(3JHjjf cPH GdeaJQi ajeG fSH Edi GdEeGe CHj GdMSf GdCTYQis - (3Ydj Hf GdMSf Hf gHI Gddg GdTGaYj GdOeTbj, CHh GdbGSe, KbI GdOjf, GHf YSGcQ , J (B571 (3g` s ((3CHh GdecGQe YHO GdUeO Hf CMeO Hf GdeRfLGfi s)
(3ChdgG (B:s
(3GdMeO ddg GdPi efM Cgd GdJMbjb ai JhMjOg HUGFQ hCMdGekG hTQM UOhQge HJeLjOg JhajbkG efg dge hEdgGekG s
(3BNQgG (B:s
(3dCfg djS Cgd ddcaGjI dJfGgjg ai GdYOGhI ddGFeI ahb GdfgGjI BNQ GdLRA GdKGef ef cJGH GdJHjjf s
(3GdfSNI HgG MhGTs
(3fSNI fajSI LOkGs
(3bQf GdfSN (B:s
(3GdbQf GdSGOSs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B4 - (3U (B273s
Keywords: (3GdJhMjO hGdedd hGdfMds